Trends in Reconstructive Neurosurgery : Neurorehabilitation, Restoration and Reconstruction - Visocchi, Massimiliano; Mehdorn, H. Maximilian; Katayama, Yoichi; von Wild, Klaus R. H. (Springer International Publishing : Imprint: Springer, 2017)
These proceeding cover new trends presented at the IV Congress of the International Society of Reconstructive Neurosurgery (ISRN), 2015. ISRN is an "open" multidisciplinary society that deals with advances in spine and peripheral-nerve reconstructive surgery, central nervous system revascularization (surgical, radio interventional), neuromodulation, bioengineering and transplantation, which are the latest tools used to promote reconstruction, restoration and rehabilitation.
Keywords: Medicine.; Neurosciences.; Neurology.; Neurosurgery.; elektronické knihy; electronic books